ANALYSIS OF PROSPECTIVE PHYSICS TEACHERS’ FEEDBACK ON ONLINE PEER-ASSESSMENT IMPLEMENTATION (Jurnal Pendidikan Fisika Indonesia, 2017)
This study aimed to analyse prospective physics teachers’ feedback during the implementation of online peer-assessment in Teaching Physics in English course. Twenty prospective physics teachers participated in this study. They were familiar with the use of smart phone in their daily life. They tend to communicate using social media such as WhatsApp application. The students have practiced in using paper based peer-assessment in other courses, but they have not applied it in online method providing real time feedback and score. The implementation of online peer-assessment challenged the students to assess their peer objectively. The lecturers’ feedback influence students’ skills how to evaluate their peer performance. Several factors may influence the quality of students’ online peer-assessment such as students’ culture back ground, implementation of the online peer-assessment, and practicant’s performance.